PENGARUH MOTIVASI DAN PELATIHAN TERHADAP DINAMIKA KELOMPOKTANI DI KABUPATEN DONGGALA - Akrab, Ali (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study aimed to determine the effects of motivation and training, both simultaneously and individually, on the dynamics of farmer groups in Donggala Regency. The research utilized a survey method, including field observations, interviews, and questionnaires distributed to 66 farmers. Data were analyzed using multiple linear regression. The F-test demonstrated that motivation and training simultaneously had positively significant influence on the group dynamics. Specifically, the t-test results revealed: (1) motivation has a positive and significant effect on the farmer group dynamics, and (2) training also has a positive and significant effect on the group dynamics. The first hypothesis test (F-test) indicated that the combined effect of motivation (X1) and training (X2) on group dynamics in Donggala Regency yielded a regression value of 87.2, with an R² score of 76.0%. The second hypothesis test (t-test) showed that motivation (X1) significantly affects the group dynamics, with a t-value of 4.520 (α = 0.05). Training (X2) also significantly affects the group dynamics, with a t-value of 5.163, and a regression coefficient of 0.460, both at a significance level of 0.05.